PATHLOSS PREDICTION MODEL IN WLAN PROPAGATION - Ayidu, Nneka Joy; Elaigwu, V. O. (FUDMA Journal of Sciences, 2023)
Pathloss propagation in urban, suburban, and rural environments has a significant impact on wireless communication networks. Different propagation models have been developed for network locations. The different terrains are unique in their topological features and environmental factors. Therefore, a propagation model suitable for one terrain may not be suitable for another propagation environment for pathloss prediction. This paper proposes a signal prediction model with an 802.11 b/g wireless local area network (WLAN) infrastructure at 2.4 GHz. The models are backed by extensive received signal strength (RSS) measurements acquired from a free space of the primary field data at the University of Benin, Benin City, Nigeria. The study considered distance based on the received signal strength of an ad hoc network for the development of a propagation model at various distances. The collected data were analysed, and a propagation model for the network terrain was developed from the log normal shadowing model. Graphical comparisons between the average RSS value and the predicted RSS value dependent on the distance were demonstrated to reflect that the proposed model can be used to predict RSS in the given propagation environment. Consequently, the utilization of this model can significantly enhance network planning activities by accurately estimating RSS values, aiding in the identification of optimal access point placement, ensuring seamless coverage, and mitigating potential coverage gaps. The findings of this research offer valuable insights for network engineers and provide a solid foundation for optimizing wireless communication within this unique network environment.